Normalising the Digital Currency as an Innovation in Digital Banking Practice - Santhosh; Kumar Raj (PT FORMOSA CENDEKIA GLOBAL, 2022)
Modern electronic payment systems by banks and other sectors have introduced the significant innovations in recent days. This paper covers, what would be the impact if the ‘Digital Currency’ is normalised as existing physical currency in banking and other transactions. That is involving digital currency in day-to-day transactions in e-payment as digital banking practice. Effect of Digital currency in the general economy, is it a boon or bane for the society? how the general public will get affected by this technological change in money. In the study we managed to collect the primary data from the general public from various localities of Karnataka and organized their opinion about the normalizing the digital currency.